Facebook usage in the Yemen uprising: A study on selfconsciousness, behaviours and attitudes of Sana'a University student / Faisal Ali Khaled Farhan - Khaled Farhan, Faisal Ali (Institute of Graduate Studies, UiTM, 2018)
The emergence of the social network has transformed the way people communicate and share information. The use of Facebook during the uprising to oppose government malpractices is not yet. In this study, self-consciousness, behaviour and attitude of Sana'a University students towards Facebook usage during the uprising is investigated using the quantitative and qualitative method. Prior to data collection, permission to obtain data was the school authorities at Sana'a University and upon approval data reported in this study was collected. A pilot study was conducted using 50 respondents to improve the research items and structure of the research instruments. Quantitative data was collected from students between 18 and 24 years old using a questionnaire and were statistically analysed using the Statistical Package for the Social Sciences (SPSS) to address the research objectives. Multiple regression and Chi-square (x2) statistical analysis were used to address the research hypotheses…